Potencial nutricional e atividade antioxidante (in vitro) de frutos silvestres do estado da Bahia - Leal, Valdeni Dias Cerqueira (2017)
Studies conducted with the Brazilian population show the prevalence of overweight and obesity in the country. They also show changes in lifestyle, such as increased consumption of fruits and vegetables, as important sources of bioactive compounds that play an antioxidant role and help prevent chronic diseases. The existence of still unexplored Bahian flora genera, such as Myrcia, provides a perspective of the use of these fruits in human food and for commercial purposes. The objective of this work was to evaluate the nutritional value and antioxidant activity of Myrcia guianensis (Aubl.) DC fruits.andMyrcia splendens (S.w.) DC. collected in the municipality of Alagoinhas-BA. The chemical and physicochemical characteristics were determined from the analysis of the whole fruits and the bioactive compounds and antioxidant activity from the crude lyophilized extract of the pulp and peel. The nutritional value of both species studied equates to the composition of the fruits in general. The amount of phenols ((M. guianensis: 56,41 μg/mL e 42,60 μg/mL / M. splendens:160,42 μg/mL e 94,82 μg/mL), flanovonoids (M. guianensis: 9,10 μg/mL e 3,22 μg/mL / M. splendens:15,71 μg/mL e 3,76 μg/mL), total anthocyanins (M. guianensis: 1957,37 mg/mL e 2757,34 mg/mL / M. splendens:943,10 mg/mL) and monomeric anthocyanins (M. guianensis: 1668,50 mg/mL e 2035,14 mg/mL / M. splendens:587,14 mg/mL were higher than the data available in the literature. The results obtained are directed to the use of fruits in low calorie diets due to low energetic value and to the production of natural dyes and / or antioxidants by nutraceutical and pharmaceutical industries